Eksistensi Madrasah Diniyah Di Tengah Pandemi, Tergeruskah? - Saadudin Annasih; Farid Noor Romadlon (Universitas Muria Kudus, 2022)
Madrasah Diniyah is a non-formal education institution. Madrasah Diniyah is one of the institutionalizations of religious education that is deeply rooted in the midst of Indonesian society that has been running for a long time. However, the current pandemic has changed peopleâ€™s lifestyles on various aspects, including the education aspect.Â The aim of this study is to find out wether Madrasah Diniyah Education will be increasingly abandoned by some people in the midst of a pandemic. Negative changes that exist in human society will cause destruction, both in world and hereafter. There are many verses of the Quran and hadiths that allude to a change. The pandemic that is being sent down by Allah at this time is a warning, a test and is a sunatullah for His servants in creating changes that must be responded well and wisely, so that it can produce good results.